2020
DOI: 10.1002/ptr.6583
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Baicalin relieves lipopolysaccharide‐evoked inflammatory injury through regulation of miR‐21 in H9c2 cells

Abstract: Myocarditis is a common heart disease which lacks effective treatment till now.Baicalin possesses plenty of activities, including anti-inflammation. In this investigation, we attempted to investigate the influences of Baicalin on Lipopolysaccharide (LPS)-evoked H9c2 cells.Cells viability, apoptosis, and expressions of apoptosisassociated proteins were, respectively, measured utilizing CCK-8 assay, flow cytometry and western blot. The levels of IL-6 and TNF-α were detected through enzyme-linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Antimicrobial peptides (AvBD1, AvBD2, and AvBD4) and Lyz are important components of the intestinal chemical barrier, which can protect the intestinal mucosa from damage ( Fusco et al, 2021 ). In addition, multiple studies have found that BA can strengthen the intestinal barrier and maintain intestinal health by affecting multiple functions of the body, including alleviating the inflammatory response and enhancing antioxidant capacity ( Liu et al, 2020 ; Rizzo et al, 2021 ). Notably, the results of the present study showed that after APEC infection, the mRNA and/or protein levels of TJs, MUC2, AvBDs, and Lyz were markedly downregulated, indicating that the intestinal barrier had been destroyed; these results are consistent with Wu et al (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides (AvBD1, AvBD2, and AvBD4) and Lyz are important components of the intestinal chemical barrier, which can protect the intestinal mucosa from damage ( Fusco et al, 2021 ). In addition, multiple studies have found that BA can strengthen the intestinal barrier and maintain intestinal health by affecting multiple functions of the body, including alleviating the inflammatory response and enhancing antioxidant capacity ( Liu et al, 2020 ; Rizzo et al, 2021 ). Notably, the results of the present study showed that after APEC infection, the mRNA and/or protein levels of TJs, MUC2, AvBDs, and Lyz were markedly downregulated, indicating that the intestinal barrier had been destroyed; these results are consistent with Wu et al (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin (C21H18O11) is a flavonoid extracted from the natural plant Scutellaria baicalensis that has biological functions such as anti-inflammatory ( 21 ), anti-oxidant ( 22 ), and anti-viral effects ( 23 ). For example, baicalin can reverse LPS-induced inflammation in H9c2 cells ( 24 ). Baicalin exerted anti-oxidant effects against lung injury ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, baicalin can effectively inhibit the growth of human herpes virus type 6 (Chen & Zhang, 2012 ). Baicalin has obvious therapeutic effects on viral myocarditis in humans, and its therapeutic mechanism may be related to miR21 (Liu et al., 2020 ). Baicalin can inhibit the activity of H 1 N 1 /H 3 N 2 influenza viruses in mice at the cellular level and in vivo (Ding et al., 2014 ) and its mechanism may involve the suppression of neuraminidase activity (Jin et al., 2018 ).…”
Section: Anti‐viral Effects Of Baicalinmentioning
confidence: 99%